Collins introducing English to young children spoken language - Dunn, Opal (HarperCollins Publishers, 2013)
A practical teacher guide book for teaching spoken English to young children Easy to read and full of practical information, Introducing English to Young Children: Spoken Language explains how very young and young children begin to acquire English, suggesting how teachers and parents can 'tune into' young children's developmental needs and support them. * Introduces lesson plans and a wide selection of useful oral activities for 3- to 8-year-olds. * Includes tips for classroom management * Contains projects, games and simple picture books that can be used from the first lessons * Includes essential information on the expectations and needs of children in the classroom and oral language acquisition Suitable for teachers of all ages, backgrounds and levels of experience